ENERGY INFRASTRUCTURE ECONOMICS: MIND MAP FOR NATIONAL, REGIONAL AND WORLDWIDE SCALES - Oleksii Havrylenko; Artem Artyukhov; Oleksandr Dluhopolskyi (Соціально-економічні відносини в цифровому суспільстві)
This study aims to develop a comprehensive analytical framework for investigating energy infrastructure economics across country, regional, and worldwide scales, establishing methodological foundations and empirical evidence necessary for coordinated decision-making in the face of climate change, technological transformation, and geopolitical disruption. The research addresses the inadequacy of traditional single-scale approaches by examining complex interconnections and cascading effects of infrastructure decisions across multiple geographical levels. The investigation develops distinct analytical structures at the country, regional, and worldwide levels. The analysis reveals that energy infrastructure economics operates within complex webs of interconnections across geographical scales, each presenting distinct analytical challenges and methodological requirements. Country-level investigations provide granular precision but are constrained by limited scope in addressing cross-border spillovers. Regional investigations emerge as critical intermediate scales that balance national specificity with broader coordination perspectives, achieving economies of scale through cooperation while facing significant coordination challenges. Worldwide investigations provide essential insights into global trends but operate with high abstraction levels and uncertainty that may limit direct policy applicability. The study identifies significant governance gaps in current cross-scale coordination approaches, particularly in policy harmonization, benefit-sharing mechanisms, and risk management. Traditional single-scale approaches to energy infrastructure economics are insufficient for addressing the multifaceted challenges of energy system transformation. The research establishes that effective energy infrastructure economics must account for complex interconnections between local, regional, and global considerations while addressing unique analytical challenges at each scale. Success in achieving sustainable and secure energy systems requires technological innovation and institutional innovation in analytical approaches, financing mechanisms, and coordination frameworks. The framework provides foundations for integrated approaches to energy infrastructure economics. However, substantial additional work is required to translate conceptual insights into practical decision-making tools for the unprecedented scale and urgency of required infrastructure transformation.